2023
DOI: 10.1002/adhm.202202622
|View full text |Cite
|
Sign up to set email alerts
|

“Cluster Bomb” Based Bismuth Nano‐in‐Micro Spheres Formed Dry Powder Inhalation for Thermo‐Radio Sensitization Effects of Lung Metastatic Breast Cancer

Abstract: Lung metastatic breast cancer (LMBC) is mainly diagnosed through CT imaging and radiotherapy could be the most common method in the clinic to inhibit tumor proliferation. While the sensitivity of radiotherapy is always limited due to the hypoxic tumor microenvironment and high doses of irradiation easily induce systemic cytotoxicity. Metal‐based materials applied as radiosensitizers have been widely investigated to improve efficiency and reduce the doses of irradiation. Herein, it is aimed to overcome these pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The results demonstrated a notable reduction in tumor volume in both the NIR and IR groups, with the combined treatment of radiotherapy and photothermal therapy exhibiting superior effects compared to monotherapy. Western blotting indicated that the synergistic effect of these treatments downregulated the expression of Snail and upregulated the expression of E-cadherin, effectively inhibiting tumor metastasis ( 90 ).…”
Section: Preclinical Application Of Micron/nddsmentioning
confidence: 99%
“…The results demonstrated a notable reduction in tumor volume in both the NIR and IR groups, with the combined treatment of radiotherapy and photothermal therapy exhibiting superior effects compared to monotherapy. Western blotting indicated that the synergistic effect of these treatments downregulated the expression of Snail and upregulated the expression of E-cadherin, effectively inhibiting tumor metastasis ( 90 ).…”
Section: Preclinical Application Of Micron/nddsmentioning
confidence: 99%
“…In particular, radiosensitizers in the form of metal nanoparticles with high atomic number ( Z ), which are deposited in tumor tissue and have a dose-increasing effect, are preferred as an alternative therapeutic route that can overcome the mentioned limitations and improve the therapeutic window . Some high- Z metal nanoparticles have been proposed for breast cancer treatment, such as gadolinium ( Z = 64), hafnium ( Z = 72), tantalum ( Z = 73), gold ( Z = 79), and bismuth ( Z = 83). Bismuth (Bi), which has the highest Z among these elements and is biocompatible and stable in forms such as sulfur and oxide, has been shown to have a greater radiosensitization effect when the particle size, concentration, and area of influence of bismuth nanoparticles are the same compared to gold and platinum nanoparticles, and they have been used in the treatment of breast cancer to increase therapeutic efficacy as radiosensitizer nanoparticles. …”
Section: Introductionmentioning
confidence: 99%
“…Metastasis is the result of the spread of tumor cells to foreign organs and stands as a primary contributor to the high lethality of cancer. [1][2][3][4] Lungs are one of the organs most susceptible to colonization by cancer cells, given their integral role in the circulatory metabolic system. 5,6 Lung cancer exhibits the highest mortality rate nationwide, and the majority (44%) of lung cancer patients are diagnosed with metastatic disease with a five-year relative survival rate of only 8%.…”
Section: Introductionmentioning
confidence: 99%